PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN SEKOLAH UNGGUL BERBASIS NILAI-NILAI ISLAM - Rosa Melinda; Istanto, Istanto (Universitas Negeri Surabaya, 2025)
This study aims to describe the principal’s leadership in realizing an excellent school at SMP IT MTA Karanganyar and to identify the supporting factors. Using a qualitative approach with a phenomenological method, data were collected through observation, in-depth interviews, and document analysis. The results show that the principal applies a transformational leadership style that is visionary, inspiring, and participatory, focusing on strengthening four flagship programs: Tahsin (Qur’anic reading), Tahfidz (Qur’anic memorization), Character Building, and ICT-Based Learning. The success of these programs is supported by the active involvement of teachers, the principal’s exemplary behavior, adequate facilities, parental support, and a structured system of evaluation and appreciation. Challenges such as the diverse backgrounds of students are addressed through personalized approaches and continuous mentoring. These findings emphasize that effective school leadership plays a central role in fostering a religious, excellent, and technologically adaptive school culture.